MENELAAH PERILAKU KEPATUHAN WAJIB PAJAK YANG TERDAFTAR PADA KPP PRATAMA PALU - Eka Indriyani MS; Herliana Herliana (Bongaya Journal for Research in Accounting (BJRA), 2020)
As assets that encourage tax revenue growth in the country, taxpayers have different views on will, desire, and freedom factors, which affect their daily behavior. Taxpayers are given a policy of implementing a self-assessment system as a form of independent implementation of tax obligations, but do not deviate from tax legislation. This research contributes to compliance by taxpayers registered with KPP Pratama Palu in central Sulawesi. The predictive factors are the views on tax corruption and tax avoidance after sampling by using 44 samples obtained by the Slovin formula and using multiple regression analysis. The results show that all exogenous variables partially and simultaneously improve taxpayer compliance. This shows that all factors affecting the tax compliance variables registered with the Palu Primary Taxation Bureau have their role.